COVID-19 mRNA Vaccines May Cause False Reactivity in Some Serologic Laboratory Tests, Including Rapid Plasma Reagin Tests. Issue 2 (30th March 2022) - Korentzelos, Dimitrios; Baloda, Vandana; Jung, Yujung; Wheeler, Bradley; Shurin, Michael R; Wheeler, Sarah E
Abstract: Objectives: Acute viral infections and some vaccines have been shown to increase false positivity in serologic assays. We assessed if the messenger RNA coronavirus disease 2019 (COVID-19) vaccines could cause false reactivity in common serologic assays in a pilot longitudinal cohort. Methods: Thirty-eight participants with sera available prevaccination, 2 weeks after each vaccine dose, and monthly thereafter for up to 5 months were tested for common infectious disease serologies and antiphospholipid syndrome (APS) serology markers on the BioPlex 2200, Sure-Vue rapid plasma reagin (RPR), and Macro-Vue RPR. Twenty-two participants received the Moderna vaccine and 16 received the Pfizer vaccine. Results: Most assays had no change in reactivity over the course of the sample draws, including APS markers. Epstein-Barr virus immunoglobulin G (IgG), measles IgG, and rubella immunoglobulin M all had possible false reactivity in one to two participants. RPR tests demonstrated false reactivity, with baseline nonreactive participant samples becoming reactive following vaccination. There were more false reactive participants (7/38) in the BioPlex RPR than in the Sure-Vue (2/38) and Macro-Vue (1/38) tests. All falsely reactive RPR tests were in participants who received the Moderna vaccine. Conclusions: Serologic assays with results that do not fit the clinical picture following COVID-19 vaccination should be repeated. Effects of false reactivity can last more than 5 months in some assays. In particular, RPR is susceptible to false reactivity, and there is variability among assays. Larger longitudinal studies are needed to determine the incidence and window of false reactivity.